B-Flow Twinkling Sign in Preoperative Evaluation of Cervical Lymph Nodes in Patients with Papillary Thyroid Carcinoma. (26th June 2013) - Napolitano, Giuseppina; Romeo, Antonio; Bianco, Andrea; Gasperi, Maurizio; Zeppa, Pio; Brunese, Luca
Abstract : Papillary thyroid cancer (PTC) is the most common histologic type of differentiated thyroid cancer. The first site of metastasis is the cervical lymph nodes (LNs). The ultrasonography (US) is the best diagnostic method for the detection of cervical metastatic LNs. We use a new technique, B-flow imaging (BFI), recently used for evaluation of thyroid nodules, to estimate the presence of BFI twinkling signs (BFI-TS), within metastatic LNs in patients with PTC. Two hundred and fifty-two patients with known PTC were examined for preoperative evaluation with conventional US and BFI. Only 83 with at least one metastatic LN were included. All patients included underwent surgery; the final diagnosis was based on the results of histology. The following LN characteristics were evaluated: shape, abnormal echogenicity, absent hilum, calcifications, cystic appearance, peripheral vascularization, and BFI-TS. A total of 604 LNs were analyzed. Of these, 298 were metastatic, according to histopathology. The BFI-TS showed high values ​ ​ of specificity (99.7%) and sensitivity (80.9%). The combination of each conventional US sign with the BF-TS increases the specificity. Our findings suggest that BFI can be helpful in the selection of suspicious neck LNs that should be examined at cytologic examination for accurate preoperative staging and individual therapy selection.